The neurobiology of functional neurological disorders characterised by impaired awareness - Milano, Beatrice Annunziata; Moutoussis, Michael; Convertino, Laura (Frontiers in Psychiatry, 2023)
We review the neurobiology of Functional Neurological Disorder (FND), namely, neurological disorders not explained by currently identifiable histopathological processes, in order to focus on those characterized by impaired awareness (functionally impaired awareness disorders, FIAD), and, especially, the paradigmatic case of Resignation Syndrome (RS). This comprehensive review provides a better, more integrated theory of FIAD, able to guide both research priorities and the diagnostic formulation of FIAD. We first describe the spectrum of clinical presentations of FND with impaired awareness. We systematically describe this diversity and suggest a new classification of FIAD. We find that an understanding of the historical development of neurobiological theory of FIAD is of paramount importance for its current understanding. Then, we review and integrate contemporary clinical material in order to contextualize the neurobiology of FIAD within social, cultural, and psychological perspectives. Thus, we use a neuro-computational approach to FND to arrive at a more coherent account of FIAD. FIAD may be based on maladaptive predictive coding, shaped by stress, attention, uncertainty, and, ultimately, neurally encoded beliefs and their updates. We also critically appraise arguments in support of and against such Bayesian models. Finally, we discuss implications of our theoretical account and provide pointers towards an improved clinical diagnostic formulation of FIAD. We suggest directions for future research towards a more unified theory on which future interventions and management strategies could be based, as effective treatments and clinical trial evidence remain limited.